THE INFLUENCE OF TAX SOCIALIZATION AND TAX KNOWLEDGE ON INDIVIDUAL TAXPAYER COMPLIANCE AT TAX SEVICE OFFICE X JAMBI CITY - Rifal Dwi Putra; Ratih Kusumastuti; Derist Touriano (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
This study seeks to assess the impact of Tax Socialization and Tax Knowledge on the compliance of individual taxpayers. The investigation was carried out among individuals who submitted their annual SPT at Tax Service Office (KPP) X in Jambi CIty, with a sample size of 74 taxpayers. Data were collected through a questionnaire utilizing the simple random sampling method. The analysis involved multiple linear regression using the SPSS 25 application. The findings indicate a significant influence of both tax socialization and tax knowledge on individual taxpayer compliance. The simultaneous F-test results demonstrate a significant combined effect of tax socialization and tax knowledge, with a coefficient of determination of 54.8%, while 45.2% is attributed to other factors. The partial t-test results reveal that the regression coefficients for tax socialization and tax knowledge variables are statistically significant, with respective coefficients of 0.027 and 0.249 at a significance level of 0.05, and P values of 0.003 and 0.006